Communication Network Simulation for Smart Metering Applications: A Review - Dahunsi, Folasade; Olayanju, Sunday; Ponnle, Akinlolu; Sarumi, Oluwafemi (Bursa Teknik Üniversitesi, 2021)
Many countries are witnessing the deployment of millions of smart meters, as they strive to upgrade their traditional grid to the smart grid already prominent in the developed parts of the world. Communication networks that can offer high-speed communication will be required for transmission of the copious amount of data resulting from the numerous smart meters and other intelligent electronic devices (IEDs) in the distribution network substation. Therefore, there is a need to critically assess the available communication infrastructure for eventual upgrade and deployment. In this paper, a survey of the communication network and networks simulation software used for this purpose was carried out, with specific emphasis on smart metering applications. Some critical requirements identified are security, quality of service (QoS) and optimal cost for system operation. Also discussed are methods employed in the works of literature to handle the critical issues raised. For data transmission between the meters and data concentrators; power line communication (PLC) was mostly cost-effective and hence, mostly deployed. In the wireless category, ZigBee (802.15.4), Wi-Fi (802.11), and WiMAX (802.16) among others are suitable and have been successfully deployed. OPNET, NS-3, NS-2, and OMNET++ have been successfully employed for communication network simulations in smart metering applications.
Keywords: Engineering; Mühendislik